Correlation between manager’s leadership style and the implementation process of “ mother friendly hospital plan ” in selected hospitals in west of country Iran (kordestan, hamedan and Kermanshah provinces) in 1391. - Tork Zahrani, shahnaz; Ghaderkhani, golbahar; Baghestani, ahmad reza; Emami, hassan (Advances in Nursing & Midwifery, 2014)
Abstract Background and Aim: Regarding the worldwide efforts to implement and improve mother friendly services, and the rights of mothers for receiving quality care , there is a need for effective leadership and management of these hospital resources. Research in health sectors has shown that managers’ leadership style is related to effectiveness, efficiency, productivity. The purpose of this study, was to examine the relationship between leadership style and implementation process of the “mother friendly Hospital Initiative” in selected hospitals in the West Country (province of Kurdistan, Hamedan and Kermanshah) in 1391 . Materials and Method: The study had a descriptive, correlational design. leadership style was measured by two questionnaires using a 5 point Likert scale, and a checklist for assessing the implementation of mother friendly services. The questionnaire were completed by managers and hospital personnel. The sample of the study consisted of 37 managers and 333 employees in selected hospitals in the provinces of Kurdistan, Hamedan and Kermanshah participated in this study. Initiatives process of The mother friendly hospital was evaluated by the monitoring list of mother friendly hospital in ministry of health. Validity of the questionnaire was assessed by content validity method and , the reability of the questionnaires was determined by internal consistency (r=0.798) for managers, (r=0.89) for staff, and the reability of the monitoring check list of mother friendly hospital was assured by inter-rater method (r=0/885). Data were analyzed done by Chi-square, Fisher Exact Test, Pearson correlation and one way anova tests using the SPSS software (version 16). Finding: The results showed that leadership style of managers’ views are as follows: 67.6% Management consulting style, 24.3% benevolent- Autocratic style and the leadership style of 8.1% was Participative. While 61% from the employee’s perspective, leadership styles used by managers, was benevolent-Autocratic, 21.3% consulting, 14.4% Autocratic – exploitation, 3.3% participative. 1393 راهب ،84 هرامش ،24 هرود / 10 ناراکمه و ینارهز کر ت زانهش It can be said that the results were Relatively satisfactory in about the process of implementing measures in mother friendly hospitals, and There is significant relationship between the leadership style employed in the first , third, Fifth, eighth and ninth proceedings in views of managers and employees from the perspective of the second , fourth and seventh steps, based on ANOVA. So th, the average ratio was higher in e authoritarian leadership style compared with and collaborative consulting style. Conclusions: The findings of this study showed that autocratic leadership style was positively correlated to more accelerated implementation of mother friendly hospital practices. Keyword: Leadership Styles, Benevolent-Autocratic Style, Autocratic – Exploitation Style, Participative Style, Consulting Styles, Mother Friendly Hospital REFERENCES Abedi,G., Hedayatizadeh,A., Rostami,F (2011) An investigation on relationship between leadership style and organizational maturity nurses in educational hospitals. World Applied Sciences Journal . 12 (7) 939-943. Akbari, F., Tavfighi, SH., Torabi, A et al (2004).[ The relationship between managers leadership style and conflict management in hospital Lorestan University of Medical Science. Journal of Lorestan University of Medical Science ,Yafteh,7 (2), Successive25.51-58 . (persian). Amerioun, A., Hosseini Shokouh, M., Karimi Zarchi, A A., Mahmoudi,N (2011). [Hospital manager’s leadership style from staff’s viewpoint and its relationship with hospital indicators.] Iranian Journal of M ilitary Medicine . 13 (3) 125-132. (persian). Arab, M., Tajvar, M ., Akbari, F., (2006). Selection an appropriate leadership style to direct hospital manpower. Iranian Journal of Public Health .5 (3) 64-69. Cherie,A., Gebrekidan,AB (2003). Nursing leadership management. produced in collaboration with the Ethiopia Public Health Training Initiative , The Carter Center, the Ethiopia Ministry of Health, and the Ethiopia Ministry of Education. Fani, AA.,Hamdan, M., Khaef Elahi, AA (2009). Design an Appropriate Model for Managing Organizations in Lebanon (Hospital Management). Humanities - Research in Management Journal, 14 (2)121-99. Available from: www.sid.ir/fa/WEVSSID/J-pdf/27713896604. Pdf. [persian]. Fen Su, S .,Jenkins, M ., Liu P E., (2011). Nurses’ perceptions of leadership style in hospitals: a grounded theory study. JCN: Journal of Clinical Nursing . 21 (1-2) 279-280. Foot, DG., (2003). Relationship of Leadership Styles and Education Levels of Nursing Administration in Long – term Care Facilitys in Five Southern State. Ph.D. Dissertation. Mississippi: Mississippi State University . Gholi zadeh , MR., Fani, AA., Ahmadvand, AM (2009) . The effect of leadership styles on job satisfaction of 1393 راهب ،84 هرامش ،24 هرود / 8 ناراکمه و ینارهز کرت زانهش police personnel. Human Development of Police Journal . 7 (28)45-29. [persian]. Ghoochani.F., Ghoochani.r (2011) [The relationship between organizational maturity and leadership in manufacturing companies]. Journal of Public Administration Perspective . 9. 182-163 .[persian]. Kenyon, M., (2009). Defining and implementing mother friendly health services: A low cost initiative to address maternal mortality in Papua New Guinea. Midwife and Reproductive Health Advisor .64 Miller Street, O’Connor, Canberra. ACT 2602. Australia. Kolagari, SH., Khoddam, H. (2006). The relationship between managers styles and staff nurse Job satisfaction, Journal of Gorgan University of Medical Sciences . 9 (3) successive 23. 68-65. (persian). Lothian, J. A (2007). The coalition for improving maternity services: Evidence basis for the ten steps of mother- friendly care introduction. Supplement The Journal of Perinatal Education.16 (1) 1s-4s. Ministryof Health and Medical Education, Office of Population and Family Health, Maternal Health Administration., (1390) (authors). A guide to Obstetric Care in Mother Friendly Hospitals . Second Edition.Tehran: Charsouye Honar Publisher (Persian). Mirmolaei, T., Dargahi, h., Kazemnejad, A., Mohager rahbari, M M (2005). Survey on midwives job satisfaction. Journal of Nursing & Midwifery , Tehran University of Medical Science, Hayat. 11 (24, 25)87-95 (Persian). Mosadegrad, AM (2005) .[ A study of relationship between leadership style managers and hospital efficiency in Isfahan University hospitals]. Faculty of Administration Sciences and Economics Journal University of Isfahan . 17 (4) 23-37. (Persian). Mosadegrad, AM., (2003). [The Relationship Between Job Satisfaction and Management Style of Managers University Hospitals in Isfahan in 1382]. Journal of Humanities and Social Sciences 4 (12)176-143. Nasiri-Poor, AA., Helali Bonab, MA., Raeisi, P (2009). [Leadership styles of health networks managers and performance indicators (East Azarbaijan Province, 2007)]. Journal of Health Management . 12 (36)54-6. (Persian). Oshagbemi,T., Gill,R., (2004). Differences in leadershipstyles and behaviour across hierarchical levels in UK organizations. The Leadership & Organization Development Journal . 25 (1) 93-106. Pourfarzad,Z., Ghamari, Z., Vanaki, Z et al (2009).[ Evaluation of leadership performance of managers in Arak educational hospitals]. Journal of Shahed University , Daneshvar, 18 (90) 59-70. (Persian). Ramey , JW. (2002). The Relationship between leadership styles of nurse manager and staff nurse Job satisfaction in hospital setting. Thesis, dissertation and capstone Paper 138.. In partial fulfillment of the Requirements for the Degree of Master of Science in Nursing. Marshall University College of Nursing and Health Professions.Huntington, West Virginia Raup, H G., (2008). The impact of ED nurse manager style on staff nurse turnover and patient satisfaction in academic health center hospitals . Journal of Emergency Nursing . 34 (5)403-40. Riahi, L et al, (2009). The survey on leadership style in health care centers of Iran University of Medical Sciences. Available from:http://darman.sums.ac.ir/nursing/images/nursing/file/rahbarimodiran.pdf[persian]. Sayedjavadi, M., Khalesi, n., Ebadifardazar,F., (2005).[ Leadership style and organizational maturity in educational hospital of Ardebil University of Medical Science]. Journal of Health Management .8 (20)95-104 . (Persian).